Mental health impact of the economic crisis in Spain - Salvador-Carulla, Luis (Int Psychiatry, 2013)
According to preliminary data, by 2010 the economic crisis in Spain had already led to an increase in the prevalence of anxiety, mood disorders and alcohol misuse, identified in primary care settings, but there had not been an impact on suicide rates. Since then, several indicators suggest that the full impact of the economic crisis on mental health was delayed, until at least the second half of 2011 and even later, to 2012. There is increasing evidence that budget cuts had a particular impact on mental healthcare during this latter period.